Integrasi Program Bantuan Sosial dalam Sistem Perlindungan Sosial Daerah: Studi Pada Pemerintah Kota Depok - Ahmad Shofwan Syaukani; Isbandi Rukminto Adi (Universitas Muhammadiyah Sorong, 2026)
This study is motivated by the implementation of social assistance programs in Depok City, This study is motivated by the fragmented implementation of social assistance programs in Depok City, where various local government agencies operate with different databases, mechanisms, and target beneficiaries. This condition risks causing benefit overlaps, inaccurate targeting, and poor coordination in poverty alleviation efforts. To address this, the Depok City Government developed the Kartu Depok Sejahtera (KDS) Program as an instrument for integrating local social assistance programs. This study aims to analyze the integration process of social assistance programs in Depok City using Heffron's (1989) public organizational characteristics framework, encompassing personal aspects, internal organizational structure and processes, and organizational transactions with the environment. A descriptive qualitative approach was employed through in-depth interviews, observation, and documentation study. The findings reveal that integration was built through regulatory strengthening, application of poverty parameters, data verification and validation, cross-agency coordination, and the development of KDS as a gateway to various local social protection programs. The study concludes that the integration of social assistance in Depok City represents a governance transformation from a fragmented system toward a more coordinated one through capacity building of actors, data and program integration, and multi-stakeholder collaboration. The sustainability of this integration is influenced by local government commitment, human resource capacity, and adaptability to changes in national policy.